Dual Learning Dynamics: Career Options for Agri‐Food Students in Kazakhstan - Bulasheva, Ainur; Gadanakis, Yiorgos; Rahman, Sanzidur (International journal of training and development, 2025)
ABSTRACT The successful implementation of the German‐originated dual learning system in various national settings inspired Kazakhstan to introduce this approach to address the shortage of specialists. The self‐employed status of professionals in the agri‐food industry raises concerns about the intentions of young individuals to remain in the industry. This study aims to identify factors influencing the intentions of students and graduates to remain with the same employer in the agri‐food industry, change employers in the same industry or leave the industry altogether. The study evaluated 651 learners undertaking dual learning (hence dual) and 217 learners undertaking traditional education (hence non‐dual). Kirkpatrick's training evaluation model provided the theoretical framework for designing satisfaction dimensions potentially influencing the career intentions of students and graduates. Multinomial Logistic Regression was used to examine the career intentions of both dual and non‐dual groups. The dual learners demonstrated a stronger association between tested factors (satisfaction and motivation) and intention to remain with the company/industry than the non‐dual learners. Despite positive outcomes in retaining skilled professionals, concerns remain regarding the career intentions of young people in the agri‐food industry. Stakeholders should provide career development opportunities and incentives to attract and retain young individuals within the agri‐food sector.